THE INFLUENCE OF COMPENSATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT SMP MULIA BUANA PARUNG PANJANG, BOGOR - Andri Priadi; Aden Prawiro Sudarso (International Journal Multidisciplinary Science, 2024)
This study examines the influence of compensation and work environment on employee performance at SMP Mulia Buana, Parung Panjang, Bogor. The importance of employee performance in achieving organizational goals is undeniable, particularly in a competitive environment. Compensation and work environment are key factors influencing employee motivation and performance. A quantitative approach was used, and data were collected through questionnaires distributed to all 66 employees at SMP Mulia Buana. The study employed multiple linear regression analysis to determine the effect of compensation and work environment on employee performance. The findings indicate that both compensation and work environment have a significant positive impact on employee performance, with the work environment showing a stronger influence. The study concludes that improving these factors can significantly enhance employee performance, ultimately aiding the organization in achieving its goals. The study recommends continuous evaluation and improvement of compensation systems and work environment conditions to further boost employee performance